FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENGGUNAAN JASA KURSUS MANDARIN DI XIN MIAO - Febrianus (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the effect of brand awareness and perceived quality on the decision to use Chinese language course at the Xin Miao Chinese Language Center through loyalty. This study is a quantitative study with a population of users of Chinese language courses at the Xin Miao Chinese Language Center with 100 respondents who using the course. The analysis technique used is the structural equation models (SEM) by using the IBM SPSS Amos 24 application. The results of this study indicate a positive and significant effect between brand awareness of decisions, perceived quality of decisions, brand awareness and perceived quality of loyalty, brand awareness and perceived quality influences purchasing decisions directly through loyalty.